Kajian Organoleptik dan Ekonomi Usaha Ayam Geprek dengan Penggunaan Berbagai Merek Minyak Goreng Komersial - Astari Ratnaduhita; Achmad Muzakky Dityana; Nur Hafidzah Devi Kartika; Muhammad Khaidar; Nida Fariha; Sukmawati Utami; Putri Ananda; Aqil Adyatama; Raditya Nandhirabrata (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aimed to analyze differences in organoleptic quality among various cooking oil brands using color, taste, texture, and aroma parameters. A sensory evaluation was conducted with 50 untrained panelists, who assessed the samples using a hedonic scale. The data were analyzed using the nonparametric Friedman test due to the ordinal scale and non-normality. The results showed highly significant differences among cooking oil brands for all organoleptic parameters (p < 0.001). Kendall’s W indicated a very strong effect size for taste (W = 0.774), followed by texture (W = 0.570) and color (W = 0.531) with strong effect sizes, while aroma showed a moderate effect size (W = 0.240). Overall, Barco achieved the highest mean score, whereas Minyakita and bulk cooking oil consistently obtained the lowest scores across most parameters. These findings demonstrate significant sensory quality differences among cooking oil brands, with taste being the most influential attribute in panelists’ perception.